Canadian healthcare capacity gaps for disease-modifying treatment in Huntington’s disease: a survey of current practice and modelling of future needs - Sylvain Chouinard; Blair R Leavitt; Angèle Bénard; Nathalie Budd; Jennifer W Wu; Kerrie Schoffer (BMJ Open)
Objectives Disease-modifying therapies in development for Huntington’s disease (HD) may require specialised administration and additional resource capacity. We sought to understand current and future capacity for HD management in Canada considering the possible introduction of an intrathecal (IT) disease-modifying treatment (DMT).Design, setting and participants Using a case study, mixed methods framework, online surveys followed by semistructured interviews were conducted in late 2020 and early 2021. Neurologists from Canadian HD (n=16) and community (n=11) centres and social workers (n=16) were invited to complete online surveys assessing current HD management and potential capacity to support administration of an IT DMT.Outcome measures Survey responses, anticipated demand and assumed resource requirements were modelled to reveal capacity to treat (ie, % of eligible patients) by centre. Resource bottlenecks and incremental support required (full-time equivalent, FTE) were also determined.Results Neurologists from 15/16 HD centres and 5/11 community centres, plus 16/16 social workers participated. HD centres manage 94% of patients with HD currently seeking care in Canada, however, only 20% of IT DMT-eligible patients are currently seen by neurologists. One-third of centres have no access to nursing support. The average national incremental nursing, room, neurologist and social worker support required to provide IT DMT to all eligible patients is 0.73, 0.36, 0.30 and 0.21 FTE per HD centre, respectively. At peak demand, current capacity would support the treatment of 6% of IT DMT-eligible patients. If frequency of administration is halved, capacity for IT-DMT administration only increases to 11%.Conclusions In Canada, there is little to no capacity to support the administration of an IT DMT for HD. Current inequitable and inadequate resourcing will require solutions that consider regional gaps and patient needs.